2016
DOI: 10.3354/cr01421
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the combined hazards of drought, soil erosion and local flooding on agricultural land: a Czech case study

Abstract: Present-day agriculture faces multiple challenges, including ongoing climate change that is at many locations combined with soil degradation. The deterioration of soil properties through unsustainable agricultural practices and changing climate could lead to a fall in productivity beyond the point of no return with devastating effects on ecosystem services in large areas. Identifying areas with the highest hazard levels should therefore be a top priority. The key hazards for agricultural land in the Czech Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…This would further increase sensitivity of regions with already high risk of drought as shown by Trnka et al . ().…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This would further increase sensitivity of regions with already high risk of drought as shown by Trnka et al . ().…”
Section: Discussionmentioning
confidence: 98%
“…The regions with high occurrence of the Cfa-and Csalike years could be thus more threatened by both phenomena in the future. This would further increase sensitivity of regions with already high risk of drought as shown by Trnka et al (2016b).…”
Section: Discussionmentioning
confidence: 99%
“…The urgency of drought risk related to recent global warming and increased drought risk in the future has been pointed out in strong terms by Trnka et al . (, ). These authors demonstrated that conditions at 45% of central European meteorological stations became significantly drier during the 1961–2014 period.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there also appears the danger of droughts; the widespread European drought in 2003 serves as an example (Beniston, 2004;Ciais et al, 2005). The urgency of drought risk related to recent global warming and increased drought risk in the future has been pointed out in strong terms by Trnka et al (2016aTrnka et al ( , 2016b. These authors demonstrated that conditions at 45% of central European meteorological stations became significantly drier during the 1961-2014 period.…”
Section: Introductionmentioning
confidence: 99%
“…Data on forest fire occurrence were obtained from the Fire Rescue Service. Indices and fire events were analyzed across the Jihomoravský region, which is considered the warmest and driest region of the Czech Republic (Trnka et al, 2016). Fig.…”
Section: Fwi Ffdi Ffimentioning
confidence: 99%